المهارات الحياتية المتضمنة في كتابي التربية الإسلامية (الفقه ـ الحديث) المقررة على طلبة الصف الثالث الثانوي في الجمهورية اليمنية - الجلال، محمد أحمد يحيى (جامعة العلوم والتكنولوجيا, 2015)
This study aimed to investigate the most important life skills that should be contained in the Islamic education textbooks (Jurispru-dence/Figh – Hadith) in the secondary schools in the Republic of Yemen. To achieve the objectives of this study, the researcher used a tool for the analysis which he had already prepared and validated. Thus, he analyzed the two courses ( biography of the prophet and Faith or Al-Eman) which are compulsory courses to the secondary school students. For the modernity of this tool and its relevance to the course, the researcher used the tool in this study as being a validated and reliable tool which consisted of seven areas with (39) skills. Findings of the Study: 1. The life skills related to the use of modern technology are not included in the two Islamic education textbooks (Jurisprudence /Figh – Hadith). 2. There is a variance in the life skills of the course “Hadith” which represented (9) skills with a significant percentage of (%23) and (15) skills by an average of (%39) and (11) skills with a low percentage of (%28) and unavailability of (4) items which represented (%10). 3. The life skills of the course “Jurisprudence” represented (4) skills which is a greater than the skills contained in the tool of the study by a percentage of (%10) and (16) skills with an average degree by a percentage of (%41) and (15) skills with low degree by a percentage of (%39), and unavailability of (4) skills which represented (%10). Recommendations of the Study: The study emphasized on the following recommendations: 1. The life skills should be included in the two courses (Hadith and jurisprudence) to a greater extent than the existing skills. 2. Life skills should be included in all the Islamic education textbooks of the public education students. By combining the life skills in the Islamic education textbooks, many problems encountered the Yemeni society can be addressed.
هدفت الدراسة الحالية إلى التعرف على أهم المهارات الحياتية التي ينبغي تضمينها في كتب التربية الإسلامية (الفقه -الحديث) في المرحلة الثانوية بالجمهورية اليمنية. ومن أجل تحقيق أهداف البحث عمد الباحث إلى استخدام أداة للتحليل سبق له أن أعدها وحكمها وفي ضوئها قام بتحليل محتوى مادتي (السيرة النبوية-الإيمان) المقررة على طلبة الصف الثالث الثانوي، ونظرا لحداثة هذه الأداة وقربها من المادة موضع التحليل عمد الباحث إلى استخدامها في هذه الدراسة باعتبارها أداة محكمة وتم التأكد من صدقها وثباتها، والمكونة من سبعة مجالات تحتوي على (39) مهارة. وكان من أهم نتائج الدراسة ما يلي: - المهارات الحياتية المتعلقة بطرق استخدام وسائل التكنولوجيا الحديثة لم تتضمن في كتابي التربية الإسلامية (الفقه-الحديث). - تباين المهارات الحياتية في مادة الحديث حيث توافرت (9) بدرجة كبيرة بنسبة (23%)، وتوافرت (15) مهارة بدرجة توافر متوسطة بنسبة (39%)، وتوافرت (11) مهارة بدرجة ضعيفة بنسبة (28%)، ولم تتوافر(4) فقرات بنسبة (10%) - توافرت المهارات الحياتية في مادة الفقه حيث توافرت (4) مهارات بدرجة (كبيرة) من المهارات التي تحتويها أداة الدراسة وبنسبة (10%)، وحصلت (16) مهارة على درجة توافر بدرجة متوسطة وبنسبة (41%)، وكذلك حصلت ((15 مهارة على درجة توافر بدرجة ضعيفة بنسبة (39 %)، وكذلك لم تتوافر فيها (4) مهارات من المهارات الحياتية وبنسبة (10%). وقد خرجت الدراسة الحالية بعدة توصيات أهمها: - التأكيد على أنه ينبغي أن تضمن المهارات الحياتية بشكل أكبر من المتوافرة حاليا في مادتي (الحديث - الفقه). - التأكيد على أنه ينبغي أن تضمن المهارات الحياتية في جميع كتب التربية الإسلامية المقررة على طلبة التعليم العام. - ينبغي التأكيد على أنه من خلال تضمين المهارات الحياتية في كتب التربية الإسلامية يمكن معالجة الكثير من المشكلات التي يعاني منها المجتمع اليمني.
763346
Keywords: المهارات الحياتية -- التربية الإسلامية -- التعليم الثانوي -- المقررات الدراسية